(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
The interaction of the anti-inflammatory drugs diclofenac and flunixin on the pharmacokinetic behavior of enrofloxacin and its active metabolite, ciprofloxacin, was studied in calves. Control group (n=10) received 5 mg/kg of enrofloxacin intramuscularly. Two weeks later the treatment was repeated and calves from group A (n=5) received 2.2 mg/kg of flunixin while group B (n=5) 1 mg/kg of diclofenac, 2 weeks later the treatments were exchanged. Heparinized blood samples were obtained at different times after application. Plasma was treated with water, homogenizing solution, and difloxacin as an internal standard. The whole was centrifuged and 50 μL of the supernatant was injected to quantify enrofloxacin and ciprofloxacin by HPLC coupled to a fluorescence detector at 295 nm excitation and 490 nm emission. Plasma concentrations vs. time of enrofloxacin and ciprofloxacin per animal were analyzed by the PK Solution 2.0 program. Intramuscular application of enrofloxacin shows rapid absorption and moderate plasma permanence. Diclofenac significantly increases Cmáx and area under the curve, while flunixin does not affect enrofloxacin kinetics. Enrofloxacin with flunixin or diclofenac co-administration modifies enrofloxacin into ciprofloxacin transformation, results that may influence the therapeutic design.